2015
DOI: 10.1530/eje-14-0990
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptor alpha is associated with prolactin pituitary tumor prognosis and supports the sex-related difference in tumor growth

Abstract: Context: A sex difference in the progression of prolactin (PRL) tumors has been disputed for years. Objective: To compare tumor characteristics and postoperative clinical course between men and women, and correlate data with estrogen receptor alpha (ERa (ESR1)) expression status. Design, patients, and methods: Eighty-nine patients (59 women and 30 men) operated on for a prolactinoma and followed for at least 5 years were selected. Tumors were classified into five grades according to their size, invasion, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 42 publications
(60 reference statements)
2
68
0
2
Order By: Relevance
“…Other studies have presented evidence that differential expression of estrogen receptor α and transforming growth factor β 1 may play a role in the difference seen in tumor pathogenesis between the genders, though the results of these studies are yet to be confirmed. 13,26 Previous studies have also shown differences in disease history between men and women with prolactinomas. Specifically, men have been previously shown to have shorter duration of symptoms prior to surgery, higher levels of preoperative serum prolactin levels, and more medically refractory disease.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have presented evidence that differential expression of estrogen receptor α and transforming growth factor β 1 may play a role in the difference seen in tumor pathogenesis between the genders, though the results of these studies are yet to be confirmed. 13,26 Previous studies have also shown differences in disease history between men and women with prolactinomas. Specifically, men have been previously shown to have shorter duration of symptoms prior to surgery, higher levels of preoperative serum prolactin levels, and more medically refractory disease.…”
Section: Discussionmentioning
confidence: 98%
“…Some attribute it to the later onset of vague symptoms resulting in delayed diagnosis, while others to the tumor biology. [12][13][14][15] Men typically present with decreased libido and impotence, whereas women tend to have more clear-cut symptoms including menstrual dysfunction and galactorrhea. 15,16 Thus far, there have also been conflicting results determining if there is a difference in response to medical treatment in males and females.…”
Section: Introductionmentioning
confidence: 99%
“…It is also recognised that lactotroph tumours in men (37,38) and silent corticotroph (ACTH positive) tumours demonstrate a more aggressive course, and may recur earlier than silent gonadotroph tumours (39,40,41). Rarely, initially silent corticotroph tumours may evolve to secrete ACTH after many years of follow-up, and this transformation may also herald more aggressive tumour behaviour (42,43,44,45).…”
Section: Reasoningmentioning
confidence: 99%
“…Dopamine-resistant lactotroph tumours often are invasive macroadenomas, and according to some studies are more angiogenic and more proliferative (84). The resistant tumours often express a lower number of dopamine D 2 receptors and ER receptors (38); other mechanisms have been proposed (85). Furthermore, high doses, up to 11 mg/week, have been shown to result in prolactin normalisation in most patients (86) (Supplementary Table 5).…”
Section: Dopamine Agonistsmentioning
confidence: 99%
“…E. Delgrange и соавт. [19], показали, что низкая экспрессия ЭРα ассоциируется с инвазивным ростом ЛАГ и резистентностью к лечению агонистами дофамина, и предлагают рассматривать отсутствие экспрессии ЭРα как вероятный показатель неблагоприятного прогноза.…”
Section: Discussionunclassified